Legal spectatorship: slavery and the visual culture of domestic violence - Moore, Kelli (Duke University Press, 2022)
Authenticating domestic violence : image and feeling in abolitionist media -- Battered women in a cybernetic milieu -- Authenticating testimony in the domestic violence courtroom -- Incorporating camp in criminal justice.